LAPORAN BERKELANJUTAN PT. ANEKA TAMBANG DAN PT. TELEKOMUNIKASI INDONESIA SEBAGAI BENCHMARKING LAPORAN BERKELANJUTAN (SUSTAINABILITY REPORT) DI INDONESIA - Ririn Breliastiti (Universitas Bunda Mulia, 2017)
Preparation of the Sustainability Report has been a priority for the company. Many companies have realized that running a business, the company can not be separated from its responsibility to the environment and surrounding communities. In 2012 there were two state-owned companies that won the ISRA, namely PT. Aneka Tambang as the Best Sustainability Report Overall and PT. Telekomunikasi Indonesia as the Best Sustainability Report Category Services. The Company is currently not win ISRA, or not preparing SR, can learn and perform benchmarking against the two state-owned companies. PT Aneka Tambang and PT Telekomunikasi Indonesia has developed a comprehensive Sustainability Report includes economic performance, social performance and environmental performance. In the third report of the performance, the two companies presented evidence in the form of a concrete explanation of activities and the amount in figures. In two reports Sustainability Report readers can understand the activities undertaken by both companies and can clearly relate to the company's main strategy. In the Sustainability Report, the two companies have been doing CSR in connection with its business processes. Starting from suppliers, production processes and the provision of services, the customer, to post-sales. Activities carried out in an integrated and comprehensive. Keywords : Sustainabitily Report, CSR, Aneka Tambang, Telekomunikasi